IMPLEMENTATION OF MINIMUM SERVICE STANDARDS IN HULAWA VILLAGE, PAGUYAMAN DISTRICT: PENERAPAN STANDAR PELAYANAN MINIMAL DI DESA HULAWA KECAMATAN PAGUYAMAN (Jurnal Ilmu Manajemen dan Bisnis, 2023)
Research objectives is For know application standard minimum service in Hulawa Village Paguyaman Regency Boalemo .The research method used is approach qualitative with type study descriptive . method data collection used in study This is observation , interview and documentation. Technique data analysis used is technique qualitative data analysis , with stages as proposed by Miles and Haberman is data reduction , data presentation and withdrawal conclusion / verification .Research results is application standard minimum service in Hulawa Village Not yet fully walk with ok . Good standard minimum service provision and distribution information sometimes found community _ or visited at home No is at place . Standard service provision of data and information administration population in Hulawa Village must adapt with renew document already _ There is with a new format . Application standard service gift letter information in Hulawa Village it turns out encountered in the manufacturing process letter information finished For signing letter sometimes Village head / Secretary of Village No be in place . Application standard minimal service simplification service in Hulawa Village rated own lack facilities and infrastructure supporters in make letter information or administration other . Application standard minimum form of service complaint public in implementation service found public No own letters completeness management administration at the Hulawa Village Office .
Keywords: Application , Standard , Service , Minimum